1988
DOI: 10.1111/j.1526-4610.1988.hed2807477.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Abnormalities in Migraine. Preliminary Findings.

Abstract: SYNOPSIS Nine patients with migraine (5 with migraineous stroke) were investigated for defects of mitochondrial energy metabolism. During effort, blood lactate rose significantly higher in migraineurs. Muscle biopsy showed ragged‐red fibres deficient in cytochrome‐c‐oxidase activity in one case. On muscle biochemistry, depression of some respiratory chain enzymes was found for the whole group of patients, and especially in 2 for cytochrome‐c‐oxidase, succinate‐cytochrome‐c‐reductase and NADH‐cytochrome‐c‐reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1

Year Published

1989
1989
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 15 publications
2
60
1
Order By: Relevance
“…Our more recent data has demonstrated the same strong maternal inheritance bias in CVS cases without coexisting neuromuscular disease [Boles et al, submitted for publication to Am J Med Genet]. Other data supporting a mtDNA component in the pathogenesis of migraine headache and CVS include lactic acidosis in both conditions [Montagna et al, 1988;Okada et al, 1998;Boles et al, 2003a], energy depleted urine organic acid metabolite profiles in CVS [Boles and Williams, 1999;Boles et al, 2003a]; decreased oxidative phosphorylation activities in both conditions [Montagna et al, 1988;Sangiorgi et al, 1994;Boles et al, 2003a], and reduced in vivo brain phosphocreatine to inorganic phosphate ratio by 31 P magnetic resonance spectroscopy in migraine headache [reviewed in Montagna et al, 1994].…”
Section: Introductionmentioning
confidence: 78%
“…Our more recent data has demonstrated the same strong maternal inheritance bias in CVS cases without coexisting neuromuscular disease [Boles et al, submitted for publication to Am J Med Genet]. Other data supporting a mtDNA component in the pathogenesis of migraine headache and CVS include lactic acidosis in both conditions [Montagna et al, 1988;Okada et al, 1998;Boles et al, 2003a], energy depleted urine organic acid metabolite profiles in CVS [Boles and Williams, 1999;Boles et al, 2003a]; decreased oxidative phosphorylation activities in both conditions [Montagna et al, 1988;Sangiorgi et al, 1994;Boles et al, 2003a], and reduced in vivo brain phosphocreatine to inorganic phosphate ratio by 31 P magnetic resonance spectroscopy in migraine headache [reviewed in Montagna et al, 1994].…”
Section: Introductionmentioning
confidence: 78%
“…Forty years of clinical evidence has suggested that migraine might be attributable to mitochondrial dysfunction (7,31,44,47,48,53,55). Montagna et al and Sangiorgi et al (31,44) both found reduced activity levels of key mitochondrial enzymes in migraineurs.…”
Section: Discussionmentioning
confidence: 96%
“…Through this mechanism, GTN could potentially enhance the adenosine signal even when adenosine levels or adenosine receptor expression are not modified. GTN also has multiple effects on mitochondrial function, an organelle that has been suggested to play a role in the development of migraine [27,178,179]. GTN treatment was found to decrease the activity of complex I in the electron transport chain within isolated rat aortas, decreasing oxygen consumption [180].…”
Section: Adenosine and Common Headache Triggersmentioning
confidence: 99%